Родини Ulmaceae Mirb. та Celtidaceae Endl. у флорі України - Zhygalova, S.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The article presents the results of critical and systematic study of representatives of the family Ulmaceae Mirb. and Celtidaceae Endl. in the Ukrainian flora. It was found that only one species of the genus Celtis of Celtidaceae (C. planchoniana (C. glabrata) is the endemic of Crimea) is naturally grows in Ukraine, the other two species and 1 subspecies (C. australis, C. australis subsp. сaucasica, C. occidentalis) introduced and cultivated in the botanical gardens, are used in various green areas. Among the members of the family Ulmaceae there are four species and one subspecies of the genus Ulmus native to the territory of Ukraine (U. glabra, U. laevis, U. pumila, U. minor, U. minor subsp. minor). The genus Zelkova is represented in the world’s flora by six species, one of them is growing in Ukraine – Z. carpinifolia. It is cultivated in gardens and parks of the South Coast of Crimea. The article presents the checklists of families Ulmaceae and Celtidaceae, including keys to the genus and species, nomenclatural citation for each species, morphological description, the general distribution and distribution in Ukraine.